The Impact of Advice Seekers’ Need Salience and Doctors’ Communication Style on Attitude and Decision Making: A Web-Based Mammography Consultation Role Play - Fissler, Tim (JMIR Cancer, 2015)
BACKGROUND: Patients and advice seekers come to a medical consultation with typical needs, and physicians require adequate communication skills in order to address those needs effectively. It is largely unclear, however, to what extent advice seekers’ attitudes toward a medical procedure or their resulting decisions are influenced by a physician’s communication that ignores or explicitly takes these needs into account. OBJECTIVE: This experimental study tested how advice seekers’ salient needs and doctor’s communication styles influenced advice seekers’ attitudes toward mammography screening and their decision whether or not to participate in this procedure. METHODS: One hundred women (age range 20-47 years, mean 25.22, SD 4.71) participated in an interactive role play of an online consultation. During the consultation, a fictitious, program-controlled physician provided information about advantages and disadvantages of mammography screening. The physician either merely communicated factual medical information or made additional comments using a communication style oriented toward advice seekers’ typical needs for clarity and well-being. Orthogonal to this experimental treatment, participants’ personal needs for clarity and for well-being were either made salient before or after the consultation with a needs questionnaire. We also measured all participants’ attitudes toward mammography screening and their hypothetical decisions whether or not to participate before and after the experiment. RESULTS: As assumed, the participants expressed strong needs for clarity (mean 4.57, SD 0.42) and for well-being (mean 4.21, SD 0.54) on 5-point Likert scales. Making these needs salient or not revealed significant interaction effects with the physician’s communication style regarding participants’ attitude change (F (1,92)=7.23, P=.009, η(2)=.073) and decision making (F (1,92)=4.43, P=.038, η(2)=.046). Those participants whose needs were made salient before the consultation responded to the physician’s communication style, while participants without salient needs did not. When the physician used a need-oriented communication style, those participants with salient needs had a more positive attitude toward mammography after the consultation than before (mean 0.13, SD 0.54), while they changed their attitude in a negative direction when confronted with a purely fact-oriented communication style (mean −0.35, SD 0.80). The same applied to decision modification (need-oriented: mean 0.10, SD 0.99; fact-oriented: mean −0.30, SD 0.88). CONCLUSIONS: The findings underline the importance of communicating in a need-oriented style with patients and advice seekers who are aware of their personal needs. Ignoring the needs of those people appears to be particularly problematic. So physicians’ sensitivity for advice seekers’ currently relevant needs is essential.